A Reinterpretation of Legal Pluralism for Indigenous Peoples in Latin America: The Case of Arica and Parinacota in Northern Chile - Flores Velásquez, Walter Cristopher (2025)
This article seeks to analyze legal pluralism from its substantive and original nature, demonstrating its validity as a normative system that reconciles the hegemonic needs of state constructs with those of intermediate or larger collective groups, primarily with respect to indigenous peoples. Precisely on this last point, legal pluralism, from the epistemology of law, responds to an intrinsic and living need of these peoples to perpetuate their knowledge and ancestry in the construction of their own legal systems, validated within their communities, which reflect customs and practices inherited from generation to generation. The scope of this assertion allows us to see a legitimate way to substantiate that legal pluralism should be a de facto reality in Latin American constitutions, where the indigenous population component is significant but still relatively marginalized in national discussion spaces. The case of Arica and Parinacota in the far north of Chile is cited as an example.